Toward a new protection plan for Algeria's forest wealth focused on responsible citizenship: case of the Aures region - Heddar, Yamina; Djebabra, Mébarek; Saadi, Saadia (Management of Environmental Quality, 2022)
Purpose The purpose of this paper is to highlight the interest of focusing public policies for wildfire management on behavioral changes supported by sustainable development projects dedicated to the Algerian forest heritage. Thus, the Aurès region in the eastern part of Algeria will be used as an example to illustrate the proposed new strategy. Design/methodology/approach The proposed method, guided by projects' management in sustainable development, consists of developing a responsible citizenship strategy focused on behavioral changes of citizens. Therefore, the title of the proposed method: The Construct of Responsible Citizenship. Findings In order to cope with forest fires, the proposed approach highlights the interest of promoting responsible citizenship. Likewise, it outlines a tool for sustaining behavioral changes based on the principle of continuous improvement and field follow-up using a multicriteria approach known as “goal programming.” Practical implications The proposed new forest fire protection plan addresses the shortcomings in Algeria's current forest fire management policy, which appears unable to deal with the increasing severity of forests' fire risk that the country has been experiencing in recent decades. Originality/value The aim is to highlight the interest of investment in forest fires prevention within the framework of the sustainable development of Algerian forest heritage, specifically, to work toward citizen subcontracting of the Algerian forest heritage.